A new joint geo-opportunistic routing scheme in duty cycled internet of underwater things. (1st March 2023) - Alghamdi, Turki Ali; Javaid, Nadeem
The inefficient consumption of energy is a critical challenge in internet of underwater things (IoUTs) because of difficult replenishment of energy. It is possible to overcome this difficulty by introducing sleep-awake scheduling for energy conservation. In this paper, two schemes have been proposed focusing on energy efficiency: geo-opportunistic asynchronous sleep-awake scheduling routing technique (GOASST) and coordinated sink mobility-based GOASST (CSM-GOASST). By exploiting geographic and opportunistic routing paradigms, the advantages like path diversity and improved reliable communication have been achieved. Moreover, the coordinated sink mobility in multi-sink architecture introduced in CSM-GOASST exhibits potential in reducing end-to-end network delay. In CSM-GOASST, an optimal sink position helps to find the shortest path to deliver data to the destination. In addition, linear programming-based mathematical modelling is carried out for performance parameters to find feasible solutions. The performance of the proposed schemes is evaluated by performing extensive simulations.